(untitled) (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2025)
The intention of this article is to analyse some of the different ways in which the interactivity of inanimate objects has been discussed, with particular reference to images. In this context, it will be also proposed to consider a type of images, here called imagin-actions, which have specific characteristics different from those already considered in the debate. There is an extensive literary tradition according to which agency has since time immemorial been attributed to inanimate objects. Indeed, thanks to the imagination, human beings naturally relate to objects, and this would in fact constitute one of the fundamental elements for the development of the human mind. Now, with the advent of digital technologies, the actions of objects and images have acquired an operational quality, since they are capable of acting directly and concretely on the living world, and also of determining specific imaginative processes that entail the responsivity of things. However, in addition to having their own agency and operativity, imagin-actions do something more: they keep users in constant motion. By responding to a series of requests, they ask for something in return, intensifying the level of interactive exchange between people and things and inevitably reconfiguring human creative processes.